Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Keterampilan Proses Sains Pada Materi Sel Kelas XI SMA - Suwahru, Annisa; Bahri, Arsad; A. Mu'nisa, A. Mu'nisa (Biology Teaching and Learning, 2018)
Abstract. Â This study aims to create a learning material product contains scientific process activities for increasing the activity and optimize skill of student which is valid. The development study has done refers to ADDIE model with five processes that, analyze, design, development, implementation, and evaluation. Based on analysis of the result of validation test, this cell worksheet has validity value for 80,6%, so it is valid. This result refers metabolism student worksheet is valid. Keywords:Â student worksheet, addie, scientific process, and cell.